PERANAN PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PEDESAAN (PUAP) TERHADAP PENINGKATAN PENDAPATAN PETANI - Sasmita Siregar; Gustami Harahap; Evi Erawati Erawati; Yudha Andriansyah Putra (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2013)
This study was conducted to determine the socio-economic developments that occurred after the Rural Agribusiness Development Program (PUAP). Determination of the area is purposive, ie areas that are already running program PUAP by purposive random sampling method sampling (random accident). Results of hypothesis testing known that Rural Agribusiness Development Program provide a positive influence on society, especially in the field of capital. Evaluation of the implementation of the Rural Agribusiness Development program conducted to see the development of the field. Implementation Jeumpa PUAP in Kuta village is still in the form of Gapoktan and has not developed into MFIs. Rural Agribusiness Development program that BLM PUAP, Guidance Counseling, and Loan Repayment PUAP BLM greatly influence the attitudes of farmers and developing a Rural Agribusiness Program (PUAP) can provide improved field of farmer income increased by 0.16%Keyword : PUAP